2013
DOI: 10.1016/j.bbamcr.2013.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal domain of A1/Bfl-1 regulates its anti-inflammatory function in human endothelial cells

Abstract: A1/Bfl-1 is a NF-κB dependent, anti-apoptotic Bcl-2 family member that contains four Bcl-2 homology domains (BH) and an amphipathic C-terminal domain, and is expressed in endothelial cells (EC). Based on NF-κB reporter assays in bovine aortic EC, we have previously demonstrated that A1, like Bcl-2 and Bcl-xL, inhibits NF-κB activation. These results, however, do not fully translate when evaluating the cell’s own NF-κB machinery in human EC overexpressing A1 by means of recombinant adenovirus (rAd.) mediated ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 38 publications
1
8
3
Order By: Relevance
“…However, expression of full length A1, using rAd.A1, in bovine ECs gave the same result as in human cells with respect to IKBα degradation [35]. These authors concluded that full length A1 does not inhibit NF-kB activation.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…However, expression of full length A1, using rAd.A1, in bovine ECs gave the same result as in human cells with respect to IKBα degradation [35]. These authors concluded that full length A1 does not inhibit NF-kB activation.…”
Section: Discussionsupporting
confidence: 66%
“…A1 has four Bcl-2 homology (BH) domains in addition to a C-terminal domain containing an amphipathic tail. Expression of fulllength A1 by recombinant adenovirus (rAd) has been shown to protect human ECs from staurosporine [35] and TNFinduced cell death [15]. This may be due to both the BH4 and C-terminal domains of this molecule, both of which have been reported to be involved in the anti-apoptotic function of A1 [36].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations